جودة الحياة المهنية وعلاقتها بالروح المعنوية لدى أساتذة التعميم المتوسط بالأغواط - دراسة ميدانية - العايب يونس; شلامة عبد القادر; لبصير سفيان (My University, 2018)
The present study aimed at exploring the relationship between the quality of professional conditions and life with middle school teachers’ state of mind and productivity .Moreover , this projects attempted to investigate the current quality of the teahers ‘ professional conditions ,mood and psychological comfort .The project tried to probe the differences between the main research variables at the middle schools in the city of Laghouat during the school year 2017/2018 in the light of some confounding variables such as gender , social status ,and professional experience. The descriptive method was adopted to meticulously study the sample which was composed of 50 teachers , the sample was randomly chosen .In terms of the research tools , the researchers have utilised two tests .The first one was the Quality of Professional Conditions Test (2010) devised by The International Islamic Association of Professional Health and Security .The second test was the State of mind Test administered by Al Rifaai (2006).The data generated by the aforementioned tools was statistically processed using the prominent statistical software SPSS17. The research work has demonstrated that : -Middle school teachers in the city of Laghouat work in high quality professional conditions . -Middle school teachers in the city of Laghouat have an optimal state of mind . -The quality of professional conditions and teachers state of mind were proven to correlate . -There are no difference between middle school teachers in terms of professional conditions and state of mind that could be related to the gender or sex variable . -The professional experience and the social status do not affect middle school teachers’ quality of professional life .Quality of professional life and conditions, state of mind, middle school teachers.